The effect of gallery walks on the Biology students’ performance in Nigerian senior secondary school - Ogundiwin, Oluyemi Akinleye; Adewumi, Gabriel Segun; Oladipo, Adenike Julianah; Adeoye, Gabriel Ademakinwa (Universitas Ahmad Dahlan, 2025)
The purpose of this research was to understand how the gallery walks method impacts the academic achievement of Biology students at the Senior Secondary level in Isin Local Government Area of Kwara State in Nigeria. The researchers utilized the pretest-posttest control group quasi-experimental design. The sample population included 103 SSII Biology students from two schools within Isin Local Government Area of Kwara State, Nigeria, who were randomly assigned to the treatment group. The instrument utilized was the Biology Student Performance Test (r=0.81). This research study followed two guiding research questions and hypotheses. The research questions were answered with descriptive statistics of means and standard deviations, while the hypotheses were tested using inferential statistics of Analysis of Covariance: all at 0.05 significance level. The findings from this research indicated that the use of the gallery walks method enhances students' performance in Biology compared to the lecture method. There exists a considerable difference concerning the average academic performance of students taught biology using the gallery walks method in contrast to those taught using the lecture method. The authors concluded that biology teachers should implement the gallery walks technique in instructing biology at the senior secondary level in order for students to learn more effectively and rapidly; also, the method is able to enhance students' self-esteem while improving their academic achievements.